PENGARUH EFEKTIVITAS PROGRAM PELATIHAN TERHADAP KINERJA KARYAWAN (Studi pada PT.Kereta Api Indonesia Daerah Operasional V Purwokerto ) - Syaezaar Pratama (Bandung Conference Series: Business and Management, 2022)
Human resources are a very important asset in a company. Therefore, it is very important for companies to have employees who have high productivity, have responsibility and work optimally so that company goals can be achieved and employees have good performance.This study aims to: 1) To determine and analyze the effectiveness of the training program at PT. Kereta Api Indonesia Daop V Purwokerto. 2) To find out and analyze the performance of employees at PT. Indonesian Railways Daop V Purwokerto. 3) To find out and analyze how much influence the training program has on employee performance at PT. Indonesian Railways Daop V Purwokerto. The sampling technique used a random sampling technique. This study uses descriptive methods and verification methods with the number of respondents as many as 86 employees using field research data collection techniques and library research. The results of this study conclude that: 1) The effectiveness of the training program at PT Kereta Api Indonesia Daop V Purwokerto is in the sufficient category. 2) The performance of employees at PT Kereta Api Indonesia Daop V Purwokerto is in the sufficient category. 3) There is a low and significant effect of the effectiveness of the training program on the performance of the employees of PT Kereta Api Indonesia Daop V Purwokerto with a contribution contribution of 25%. Keywords: Effectiveness of Training Programs, Employee Performance.